Model Pembelajaran Berbasis Pendidikan Karakter pada Pembelajaran PAI Bidang Aqidah dan Akhlak di SMP - Hajriana, Hajriana (EDUCASIA: Jurnal Pendidikan, Pengajaran, dan Pembelajaran, 2016)
The research and development tries to develop model of teaching for Islamic Education Faith and Moral aspects can build student’s character and then aplicated of model in real teaching process. This research design used Research and Development (R&D) developed by Borg and Gall, was done in two phases, (1) Developing model of lesson plan based on character education for Islamic Education Faith and Moral aspects based on theoretical and empirical studies, and (2) Implementation of the model in teaching process at Junior High School of Samarinda Education Foundation. Data collection which suitable with research and development phases used expert validation, observation, interview, and documentation technique, then data were analyzed by using descriptive qualitative. The research and development finding were; (1) a model of teaching based on character education for Islamic Education Faith and Moral aspects that consists of six phases or steps; the first phase, orientation; the second phase, classification and formulation of concepts; the third phase, story presentation; the forth phase, identification and classification of values; the fifth phase, confirmation; and the sixth phase, reflection, (2) the implementation of model of teaching to formation lesson plans (RPP) and teaching process in the classroom was done well. model pembelajaran, pendidikan karakter, pendidikan agama Islam